EMBRACING THE DIGITAL FRONTIER: STRATEGIES FOR SUCCESSFUL INNOVATION ADOPTION IN THE IT SECTOR - Durge, Rushi R.; Khan, Nusrat N.; Thorat, Sachin P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As Information Technology (IT) continues to rapidly evolve, organizations within the industry are faced with the imperative to navigate the technological horizon effectively. This research paper presents an in-depth analysis of innovation adoption in IT industries, aiming to discern the intricate dynamics that shape the assimilation of emerging technologies. Drawing upon a comprehensive review of existing literature, coupled with empirical investigations into a diverse range of IT enterprises, this study synthesizes insights to offer a nuanced understanding of the multifaceted factors influencing innovation adoption. The abstract highlights the multidimensional approach employed in the research, drawing on theoretical frameworks from innovation diffusion and technology adoption literature. The central focus is on understanding the intricate interplay between organizational, technological, and environmental factors that influence how IT industries assimilate emerging technologies. The paper navigates through organizational determinants such as culture, leadership, and structure, shedding light on how these elements shape the readiness of organizations to embrace technological change. It underscores the importance of addressing challenges related to technological complexity, external environmental influences, and social dynamics in the quest to successfully adopt and integrate innovations. Furthermore, the abstract alludes to the development of a holistic theoretical framework that synthesizes insights from existing literature, offering a nuanced perspective on the innovation adoption process in IT industries. This framework serves as a guide for practitioners, policymakers, and scholars seeking to navigate the complexities of the technological horizon.